Growing up online, czyli wiedzieć i działać w świetle internetowych poradników nie tylko dla nauczycieli - Małgorzata Dagiel; Małgorzata Kowalik-Olubińska (Problemy Wczesnej Edukacji)
The aim of the article is to compare selected Internet guides for teachers and parents. The results of a comparative analysis made by the authors are as follows: institutional senders prevail in terms of a category of a guide’s sender; a creation of a reality shared by its sender and receiver takes place in the guides; the language of the guides is used mainly in the informative and persuasive functions; there is a clear tendency to exaggerate threats posed by the participation in the digital world at the cost of recognizing opportunities for development. The authors of the article conclude with the statement that the discourse of the analysed guides supports traditional approach to perceiving and upbringing of children and young people.